Customer Satisfaction on Banking Channels - Prasad, Gokul; Arthanar, Anuradha (International Journal of Marketing Research Innovation, 2017)
Satisfaction with banking services is an area of growing interest to researchers and managers.This research examined the survey responses of 120 bank customers who provided information regarding their satisfaction towards ﬁnancial distribution channels with respect to their banks. The study found that there were distinctive segments within the ﬁnancial market that had signiﬁcantly different levels of usage of ﬁnancial distribution channels. Financial customers’ satisfaction with Mobile banking, automated teller machines, credit cards, debit cards, internet banking was investigated, and this information was used to determine if relationships exist between customer satisfaction and the usage of ﬁnancial distribution channels. Systematic methodology, including design and validation of questionnaire and factor analysis were used to enhance the reliability of the ﬁndings. Further results and implications of the study for ﬁnancial services are addressed.